Topoisomerases as anticancer targets - Delgado, Justine L; Hsieh, Chao-Ming; Chan, Nei-Li; Hiasa, Hiroshi (Biochemical journal, 2018)
Many cancer type-specific anticancer agents have been developed and significant advances have been made toward precision medicine in cancer treatment. However, traditional or nonspecific anticancer drugs are still important for the treatment of many cancer patients whose cancers either do not respond to or have developed resistance to cancer-specific anticancer agents. DNA topoisomerases, especially type IIA topoisomerases, are proved therapeutic targets of anticancer and antibacterial drugs. Clinically successful topoisomerase-targeting anticancer drugs act through topoisomerase poisoning, which leads to replication fork arrest and double-strand break formation. Unfortunately, this unique mode of action is associated with the development of secondary cancers and cardiotoxicity. Structures of topoisomerase-drug-DNA ternary complexes have revealed the exact binding sites and mechanisms of topoisomerase poisons. Recent advances in the field have suggested a possibility of designing isoform-specific human topoisomerase II poisons, which may be developed as safer anticancer drugs. It may also be possible to design catalytic inhibitors of topoisomerases by targeting certain inactive conformations of these enzymes. Furthermore, identification of various new bacterial topoisomerase inhibitors and regulatory proteins may inspire the discovery of novel human topoisomerase inhibitors. Thus, topoisomerases remain as important therapeutic targets of anticancer agents.